IMPLIKASI HUKUM DARI DOKUMENTASI TRANSFER PRICING YANG TIDAK MEMADAI DI INDONESIA - Muhammad Riza Pahlevi; Bambang Widarto (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
Transfer pricing documentation is a crucial requirement, especially for parties conducting transactions with affiliated parties, both domestically and internationally. This study aims to determine the transfer pricing provisions in Indonesia and the legal implications of inadequate transfer pricing documentation in Indonesia. The research method used is a qualitative, normative-juridical approach. Legal materials are drawn from decisions and legislation related to transfer pricing. The results of this study are: 1) Transfer pricing provisions in Indonesia are regulated by Minister of Finance Regulation Number 172 of 2023, which emphasizes the arm's-length principle for transactions between related parties, expands the scope of documentation to include financial transactions, and aligns regulations with international standards to increase transparency and tax fairness. 2) Incomplete transfer pricing documentation can result in administrative sanctions and stringent tax audits. The dispute between the Directorate General of Taxes and PT Garuda Mataram Motor emphasizes the importance of the arm's-length principle and adequate documentary evidence, while highlighting the need for an effective dispute resolution mechanism to manage tax risks for multinational companies and regulators.